Towards improved membrane production: using low-toxicity solvents for the preparation of PEEK nanofiltration membranes. Issue 8 (23rd December 2015) - da Silva Burgal, João; Peeva, Ludmila; Livingston, Andrew
Abstract : In this work it is shown that PEEK membranes are "green" from the production point of view when compared with commercial polyimide (PI) based organic solvent nanofiltration (OSN) membranes. Abstract : In this work it is shown that PEEK membranes are "green" from the production point of view when compared with commercial polyimide (PI) based organic solvent nanofiltration (OSN) membranes. Green metrics ( E -factor and solvent intensity) and waste cost were used in order to assess the environmental burden of PEEK membranes: the solvent intensity of PEEK membranes is 8.3 vs. 35–224 for PI based membranes, and the waste cost for PEEK membranes is 46 £ kg −1 of polymer vs. 1019 £ kg −1 of polymer (bench scale) and 189 £ kg −1 of polymer (industrial scale) for PI based membranes. Scaling-up of PEEK membranes to spiral-wound modules was successfully achieved with permeances between 0.26 L h −1 m −2 bar −1 and 0.47 L h −1 m −2 bar −1 for THF, and molecular weight cut-offs (MWCO) of ∼300 g mol −1 . As a final assessment, the solvent intensity and environmental burden associated with permeating a THF flow of 100 L h −1 using PEEK membranes was also assessed. The results showed a waste cost of 1.4 £ m −2 of membrane, significantly lower than PI based membranes.